Identifying Urinary and Serum Exosome Biomarkers For Radiation Exposure Using A DDA and SWATH-MS Combined Workflow - Kulkarni, Shilpa (Int J Radiat Oncol Biol Phys, 2016)
BACKGROUND: Early and accurate assessment of radiation injury by radiation-responsive biomarkers is critical for triage and early intervention. Biofluids such as urine and serum are convenient for such analysis, recent research also suggests that exosomes are a reliable source of biomarkers in disease progression. In this study, we analyzed total urine proteome, and exosomes isolated form urine or serum for potential biomarkers of acute and persistent radiation injury in mice exposed to lethal whole body irradiation (WBI). METHODS: For feasibility studies, mice were irradiated at 10.4 Gy WBI, urine and serum samples were collected 24 and 72 hr post-irradiation. Exosomes were isolated and analyzed by LC-MS/MS- based workflow for radiation exposure signatures. A DDA and SWATH-MS combined workflow approach was used to identify significantly exosome biomarkers indicative of acute or persistent radiation-induced responses. For validation studies, mice were exposed to 3, 6, 8 or 10 Gy WBI and samples were analyzed for comparison. RESULTS: Comparison between total urine proteomics and urine exosome proteomics demonstrated that exosome proteomic analysis was superior in identifying radiation signatures. Feasibility studies identified 23 biomarkers from urine and 24 biomarkers from serum exosomes post-WBI. Urinary exosome signatures identified different physiological parameters than the ones obtained in serum exosomes. Exosome signatures from urine indicated injury of the liver, gastrointestinal, and genitourinary track, whereas serum showed vascular injuries and acute inflammation in response to radiation. Selected urinary exosomal biomarkers also showed changes at lower radiation doses in validation studies. CONCLUSION: Exosome proteomics revealed radiation- and time-dependent protein signatures after WBI. 47 differentially secreted proteins were identified in urinary and serum exosomes, together these data showed the feasibility of defining biomarkers that could elucidate tissue-associated and systemic response caused by high dose ionizing radiation. This is a first report employing exosome proteomics approach to identify radiation signatures.